Designing And Optimizing Opportunistic Communication Networks (Texas Journal of Engineering and Technology, 2024)
This paper tries to address the challenge of detecting and managing overlay topologies in opportunistic networks. As a first contribution, it introduces the concept of "link" in opportunistic networks, which is different from the traditional perspective in classic MANETs: instead of an instantaneous communication relation between two nodes, links are defined here as the cumulative contacts of nodes over a time interval. This redefinition lets opportunistic networks be modeled as graphs that evolve. A key insight is that this approach enables the regulation of how nodes handle contacts to construct overlays according to a desired topology. That is important because the statistical properties of the overlay topology can form a basis for assessing a network's capacity to disseminate content. The feasibility of the proposed method is shown by a trace-driven simulation using various datasets, which range from dense urban networks to highly sparse environments. These experiments confirm that the approach effectively manages overlay topologies in opportunistic networks.